Harnessing social safety in a context of changing social contracts: compensation schemes and subsidy reforms in the GCC - Moerenhout, T (Oxford Institute for Energy Studies, 2017)
Due to the sustained low oil price in international markets and the resulting fiscal stress, GCC countries have begun reforming their energy prices. Some of these reforms are structural, and intended to last beyond the low-oil-price period. However, so far, most GCC countries have not used compensation measures to mitigate the negative impacts on households from the reforms. While the social contract proved sufficiently resilient to allow for the initial price increases from a very low base, new pricing reforms should be accompanied by the introduction of new distributive welfare methods to compensate for the adverse impact of higher energy prices on households. In their absence, growing income inequalities and public discontent could very well lead to the reversal of reforms. This paper analyses the complex nature of the development and implementation of new social safety mechanisms. It argues that while cash transfers seem the best option to compensate for loss of household welfare as a result of energy pricing reforms in the GCC, they are not a panacea to resolve the structural deficiencies of these states. The success of cash transfers will depend on their design and implementation, as well as on the introduction of complementary short-term mitigation measures. The paper concludes with key considerations for the development of more targeted and cost-effective social safety nets in the medium term. The conclusion emphasizes that a combination of subsidy reforms and cash transfers are a good start, but are still insufficient to move rentier states to productive states. This would require policy reforms in the areas of, inter alia, labour market, migration, education, and social insurance.